Media Penyiaran di Negara Industri Baru Asian (Taiwan, Korea Selatan, Singapura dan Hong Kong) dalam Era Globalisasi - Reza Aprianti (Wardah, 2015)
This study discuss the tendency of broadcast media commercialization in the four newly industrialized countries in Asia, which are known as NICs (Newly Industrialized Countries) consisting of Taiwan, South Korea, Singapore and Hong Kong. The objective of this study is to find out the characteristics of the commercial media in Asia along with the trend and limitation. Which are any changes directly or indirectly in the form of broadcasting in the Asia that much influence on the political and social system. In addition to discussing the state of the four NICs (Taiwan, South Korea, Singapore and Hong Kong), the study will also discuss other Asian countries in general. In simple terms this study assumed that: (1) the tendency of media liberalization and rules on the Asian NICs that have made great contributions for creating media commercialization. (2) The most important of the commercialization of the media against the political and social system is that the commercialization of the media can be an alternative or indirectly be the way for the success of democratic media, which would be the first step for the creation of political and social democracy in Asia.